Faktor – Faktor yang Mempengaruhi Kepuasan Pasien terhadap Pelayanan Kesehatan di UPTD Puskesmas Jatirasa - Isnaeni, Isnaeni; Cholisoh, Lilis (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Patient satisfaction is closely related to the quality of health services and is one of the measuring tools used to assess the fulfillment of patient needs and expectations in receiving health services at community health centers. Patient satisfaction depends on the quality of services provided at the Puskesmas. Quality of health services is the degree of perfection of health services in accordance with professional standards and service standards by using the potential resources available at the health center in a reasonable, efficient, effective manner and provided safely and satisfactorily according to norms. ethics, law and socio-culture by taking into account the limitations and capabilities of the government, as well as the consumer community. Knowing the factors that influence patient satisfaction with health services. Analytical with cross sectional design. The sample in this study was a portion of patients who visited the UPTD Jatirasa Health Center in January 2025, totaling 69 respondents. The sampling technique uses random sampling. The majority of respondents said they were satisfied (68.1%), good reliability (52.2%), good responsiveness (76.8%), good assurance (68.1%), good empathy (59.1%) and good tangibility (75.4%). There is an influence of Reliability, Responsiveness, Assurance, Empathy and Tangible on patient satisfaction at the Jatirasa Health Center UPTD, with a p value <0.05. There is an influence of Reliability, Responsiveness, Assurance, Empathy and Tangible on patient satisfaction at UPTD Jatirasa Health Center. It is hoped that the health service can pay attention to the needs of health workers at each health center so that health services can run as they should. Keywords: Satisfaction, Reliability, Responsiveness, Assurance, Empathy, Tangibles  ABSTRAK Mutu pelayanan kesehatan dan menjadi salah satu alat ukur yang digunakan untuk menilai pemenuhan kebutuhan serta harapan pasien dalam menerima pelayanan kesehatan di puskesmas. Kepuasan pasien tergantung pada kualitas mutu pelayanan yang diberikan di Puskesmas. Mutu pelayanan kesehatan merupakan derajat kesempurnaan pelayanan kesehatan sesuai dengan standar profesi dan standar pelayanan dengan menggunakan potensi sumber daya yang tersedia di puskesmas secara wajar, efisien, efektif serta diberikan secara aman dan memuaskan secara norma. etika, hukum, dan sosial budaya dengan memperhatikan keterbatasan dan kemampuan pemerintah, serta masyarakat konsumen. Mengetahui faktor – faktor yang mempengaruhi kepuasan pasien terhadap pelayanan kesehatan. Analitikdengan rancangan cross sectional. Sampel dalam penelitian ini adalah sebagian pasien yang berkunjung di UPTD Puskesmas Jatirasa pada bulan Januari 2025 sebanyak 69 responden. Teknik pengambilan sampel menggunakan randoom sampling. Mayoritas responden mengatakan puas (68,1%), Reliability baik (52,2%), Responsiveness baik (76,8%), Assurance baik (68,1%) , Empaty baik (59,1%) dan Tangible baik (75,4%). Ada pengaruh Reliability, Responsiveness, Assurance, Empaty dan Tangible terhadap kepuasan pasien di UPTD Puskesmas Jatirasa, dengan nilai p value < 0,05. Ada pengaruh Reliability, Responsiveness, Assurance, Empaty dan Tangible terhadap kepuasan pasien di UPTD Puskesmas Jatirasa. Diharapkan dinas kesehatan dapat memperhatikan kebutuhan tenaga kesehatan setiap puskesmas agar pelayanan kesehatan dapat berjalan sebagaimana mestinya. Kata Kunci: Kepuasan, Reliability, Responsiveness, Assurance, Empaty Tangible